Determination of protein binding for novel 2‐(2‐hydroxypropanamido)‐5‐trifluoromethyl benzoic acid enantiomers to rats, dogs, and humans plasma by UPLC‐MS/MS. Issue 5 (21st February 2020) - Rong, Rong; Wang, Xin; Dan, Yuhan; Zhang, Ruizhen; Zhao, Yunli; Yu, Zhiguo
Abstract: R ‐/ S ‐2‐(2‐hydroxypropanamido)‐5‐trifluoromethyl benzoic acid ( R‐ / S ‐HFBA) is a novel COX inhibitor with remarkable anti‐inflammatory and antiplatelet aggregation activities, but no gastrointestinal toxicity. In our previous study, the different pharmacokinetic profiles of the two enantiomers in rats were observed after administration of R ‐HFBA and S ‐HFBA. Stereoselective protein binding of the two enantiomers may be a reason for the different pharmacokinetic behaviors. In this study, we developed and validated an UPLC‐MS/MS method for determining stereoselective binding of HFBA enantiomers to rat, dog, and human plasma in vitro. Chromatographic separation was achieved by gradient elution with a flow rate of 0.4 mL/min. MS/MS detection was operated in positive electrospray using multiple reaction monitoring (MRM) mode. The method was proved to be linear over the concentration range of 0.005 to 10 μg/mL with a lower limit of quantification of 0.005 μg/mL. The developed method was successfully employed to the plasma protein binding study of HFBA enantiomers. Equilibrium dialysis method was applied to assess drug‐plasma protein interactions. The results showed that the enantiomers were both extensively bound to three species plasma and protein binding of R ‐/ S ‐HFBA was concentration dependent. R ‐HFBA and S ‐HFBA showed significant species difference among rat, dog, and human plasma and stereoselective plasma protein binding. Abstract :